Gender differences and entrepreneurial factors in psychological adjustment during organizational restructuring (2014)
Typically, organizational restructuring come with change and the challenge of what to do when there is job loss. This can impact psychological well-being for both male and female employees. Hence, the study with a sample of 496 [233 (46.9%) males and 263 (53.1%) females]. Their mean age was 39.1 years (sd=10.31). Questionnaires were used for data collection. Two hypotheses were tested with ‘Pearson r’ and t-test. Results showed positive and significant correlation between entrepreneurial factors and psychological adjustment: Entrepreneurial role models (r = 0.28, df = 494, p<.001); promotion of entrepreneurship (r= 0.11, df=494, p<.05); entrepreneurial readiness (r= 0.11, df= 494, p<.05); and subjective norms (r= 0.16, df= 494, p<.05). Gender differences was found in psychological well-being (t = 24.7; df = 494; p<.001). Males (Ẋ=13.30) significantly differ from females ( Ẋ= 7.94) on psychological adjustment. Entrepreneurial factors showed positive relationship with psychological well-being. Gender was also important. Findings implied that the factors are relevant in employees’ psychological adjustment during organization restructuring. Therefore, in preparing workforce for exercise leading to job-loss, organizations need to consider these factors as important in their staff exit/ lay-off sensitization training. This would help them to cope with the change associated with restructuring.